A spectroscopic study of the chromatic properties of GafChromic™EBT3 films. Issue 3 (8th February 2016) - Callens, M.; Crijns, W.; Simons, V.; De Wolf, I.; Depuydt, T.; Maes, F.; Haustermans, K.; D'hooge, J.; D'Agostino, E.; Wevers, M.; Pfeiffer, H.; Van Den Abeele, K.
Abstract : Purpose: This work provides an interpretation of the chromatic properties of GafChromic™EBT3 films based on the chemical nature of the polydiacetylene (PDA) molecules formed upon interaction with ionizing radiation. The EBT3 films become optically less transparent with increasing radiation dose as a result of the radiation‐induced polymerization of diacetylene monomers. In contrast to empirical quantification of the chromatic properties, less attention has been given to the underlying molecular mechanism that induces the strong decrease in transparency. Methods: Unlaminated GafChromic™EBT3 films were irradiated with a 6 MV photon beam to dose levels up to 20 Gy. The optical absorption properties of the films were investigated using visible (vis) spectroscopy. The presence of PDA molecules in the active layer of the EBT3 films was investigated using Raman spectroscopy, which probes the vibrational modes of the molecules in the layer. The vibrational modes assigned to PDA's were used in a theoretical vis‐absorption model to fit our experimental vis‐absorption spectra. From the fit parameters, one can assess the relative contribution of different PDA conformations and the length distribution of PDA's in the film. Results: Vis‐spectroscopy shows that the optical density increases with dose in the full region of the visible spectrum. The Raman spectrum is dominated by two vibrational modes, most notably by the ν (C≡C) and the ν (C=C) stretching modes of the PDA backbone. By fitting the vis‐absorption model to experimental spectra, it is found that the active layer contains two distinct PDA conformations with different absorption properties and reaction kinetics. Furthermore, the mean PDA conjugation length is found to be 2–3 orders of magnitude smaller than the crystals PDA's are embedded in. Conclusions: Vis‐ and Raman spectroscopy provided more insight into the molecular nature of the radiochromic properties of EBT3 films through the identification of the excited states of PDA and the presence of two PDA conformations. The improved knowledge on the molecular composition of EBT3's active layer provides a framework for future fundamental modeling of the dose–response.